Cultivating a Community of Scholars: Crafting a Virtual Information Literacy Hub to Support Student Research. Issue 2 (30th September 2022) - Gaylor, Ryan; Cain, Jessica; Chase, Matthew; Evener, Julie
Abstract: This paper focuses on how one university library embarked on a journey to provide information literacy instruction when a change in curriculum altered the library's role in a first-term research methods course. Enter the Scholarly Skills Community: a virtual learning landscape, consisting of more than 20 modules designed to fill gaps in information literacy and research skills. Embedded into the university's learning management system, the Scholarly Skills Community is an interactive, asynchronous destination for users to cultivate new knowledge and earn micro-credentials on topics related to information literacy and scholarly writing.